2020
DOI: 10.1186/s12902-020-00644-y
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal B-cell lymphoma with pan-hypopituitarism and oculomotor nerve palsy: a case report and review of the literature

Abstract: Background Primary nasopharyngeal lymphoma (NPL) is a very rare tumor of Waldeyer ring (WR) lymphoid tissue. It is challenging to differentiate lymphoma infiltration of pituitary from a pituitary adenoma, meningioma infiltration, and other sellar lesions to plan a suitable treatment strategy. We presented for the first time a unique case of NPL with an unusual presentation of oculomotor nerve palsy associated with pan-pituitary involvement in a diabetic patient. Case presentation A 64-year old diabetic woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…One feature of our case is the simultaneous presentation of both hemi-cranial nerve palsies and hypopituitarism with compression of the pituitary gland by a mass from sphenoidal sinus though osteolytic lesion of the sphenoidal bone. Zahedi et al reported a case of B-cell lymphoma at nasopharyngeal site in which there was presentation of both pan-hypopituitarism and oculomotor nerve palsy [ 3 ]. They also reviewed 17 cases of nasopharyngeal B-cell lymphoma, but none of the cases of nasopharyngeal B-cell lymphoma presented cranial nerve palsies nor hypopituitarism [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One feature of our case is the simultaneous presentation of both hemi-cranial nerve palsies and hypopituitarism with compression of the pituitary gland by a mass from sphenoidal sinus though osteolytic lesion of the sphenoidal bone. Zahedi et al reported a case of B-cell lymphoma at nasopharyngeal site in which there was presentation of both pan-hypopituitarism and oculomotor nerve palsy [ 3 ]. They also reviewed 17 cases of nasopharyngeal B-cell lymphoma, but none of the cases of nasopharyngeal B-cell lymphoma presented cranial nerve palsies nor hypopituitarism [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zahedi et al reported a case of B-cell lymphoma at nasopharyngeal site in which there was presentation of both pan-hypopituitarism and oculomotor nerve palsy [ 3 ]. They also reviewed 17 cases of nasopharyngeal B-cell lymphoma, but none of the cases of nasopharyngeal B-cell lymphoma presented cranial nerve palsies nor hypopituitarism [ 3 ]. Similarly, Wajima et al reviewed 15 cases of sphenoidal lymphoma [ 5 ]; 73.3% patients initially presented with ptosis or diplopia caused by II, III, IV, or VI palsy, but not hypopituitarism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microvascular ischemia is regarded as the most common cause [2], and it is closely related to diabetes [3]. In addition, differences have been reported in the incidence rates of other causes of cranial nerve palsy in diabetic patients [4, 5]. Hence, diabetic ONP should be distinguished from other etiologies of isolated ONP.…”
Section: Introductionmentioning
confidence: 99%